The Role of the Halal Value Chain Process in MSMEs on the Economy of South Kalimantan - Malihah, Lola; Sauqi, Muhammad (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2024)
Introduction: The global halal industry has grown rapidly in recent years, providing great opportunities for business actors. Indonesia, with around 242 million Muslims, accounts for 11.7% of the world's Muslim population. To monitor the development of the halal industry, clear benchmarks are needed, such as the concept of a